Real world effectiveness and safety of pegylated liposomal doxorubicin in platinum-sensitive recurrent ovarian, fallopian, or primary peritoneal cancer: a Korean multicenter retrospective cohort study - Park, Soo Jin; Kim, Jihye; Kim, Hee Seung; Lee, Jeong-Won; Chang, Ha Kyun; Lee, Keun Ho; Kim, Dae-Yeon; Kim, Sunghoon; Chang, Suk-Joon; Han, Seung Su; Park, Sang-Yoon; Shim, Seung-Hyuk (Journal of gynecologic oncology, 2020)
To evaluate the effectiveness and safety of the combination of pegylated liposomal doxorubicin with carboplatin (CD) compared with those of carboplatin and paclitaxel (CP) for platinum-sensitive recurrent ovarian, fallopian, or primary peritoneal cancer in a real-world setting in Korea. We enrolled relevant patients from 9 institutions. All patients received CD or CP as the second- or third-line chemotherapy in routine clinical practice during 2013-2018. The primary endpoints were progression-free survival (PFS) and toxicity. The secondary endpoint included the objective response rate (ORR). Overall, 432 patients (224 and 208 in the CD and CP groups, respectively) were included. With a median follow-up of 18.9 months, the median PFS was not different between the groups (12.7 vs. 13.6 months; hazard ratio, 1.161; 95% confidence interval, 0.923-1.460; p=0.202). The ORR was 74.6% and 80.1% in the CD and CP group, respectively (p=0.556). Age and surgery at relapse were independent prognostic factors. More patients in the CD group significantly experienced a grade 3 to 4 hematologic toxicity and hand-foot syndrome (13.8% vs. 6.3%), whereas grade 2 or more alopecia (6.2% vs. 36.1%), peripheral neuropathy (4.4% vs. 11.4%), and allergic/hypersensitivity reaction (0.4% vs. 8.5%) developed more often in the CP group. The safety and effectiveness of chemotherapy with CD in a real-world setting were consistent with the results from a randomized controlled study. The different toxicity profiles between the 2 chemotherapy (CD and CP) regimens should be considered in the clinical practice. ClinicalTrials.gov Identifier: NCT03562533.